Biokonjugasi AmineQDs untuk Penargetan Spesifik Sel Kanker - Permadi, Adi (Institut Teknologi Adhi Tama Surabaya, 2023)
This study aims to develop an AmineQDs bioconjugation technique to enhance specific cancer cell targeting. AmineQDs were synthesized using a solvothermal method, modified with amine groups, and conjugated with folic acid via 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide- N-hydroxysuccinimide(EDC-NHS) carbodiimide activation. This bioconjugation process aims to improve the selectivity of QDs toward cancer cells, enabling more effective detection and therapy. Characterization results indicated successful bioconjugation, but the fluorescence of QDs was quenched after conjugation, likely due to electronic structure changes or self-quenching. Further evaluation of reaction conditions, including pH and buffer types, is needed to maintain optical stability. With proper optimization, AmineQDs have the potential to serve as highly accurate and efficient nanotechnology-based cancer diagnostic and therapeutic agents.